Adipose stem cells differentiated chondrocytes regenerate damaged cartilage in rat model of osteoarthritis. (21st March 2016) - Latief, Noreen; Raza, Fahad Ali; Bhatti, Fazal‐Ur‐Rehman; Tarar, Moazzam Nazir; Khan, Shaheen N.; Riazuddin, Sheikh
Abstract: Transplantation of mesenchymal stem cells (MSCs) or autologous chondrocytes has been shown to repair damages to articular cartilage due to osteoarthritis (OA). However, survival of transplanted cells is considerably reduced in the osteoarthritic environment and it affects successful outcome of the transplantation of the cells. Differentiated chrondroytes derived from adipose stem cells have been proposed as an alternative source and our study investigated this possibility in rats. We investigated the regenerative potential of ADSCs and DCs in osteoarthritic environment in the repair of cartilage in rats. We found that ADSCs maintained fibroblast morphology in vitro and also expressed CD90 and CD29. Furthermore, ADSCs differentiated into chondrocytes, accompanied by increased level of proteoglycans and expression of chondrocytes specific genes, such as, Acan, and Col2a1. Histological examination of transplanted knee joints showed regeneration of cartilage tissue compared to control OA knee joints. Increase in gene expression for Acan, Col2a1 with concomitant decrease in the expression of Col1a1 suggested formation of hyaline like cartilage. A significant increase in differentiation index was observed in DCs and ADSCs transplanted knee joints ( P = 0.0110 vs. P = 0.0429) when compared to that in OA control knee joints. Furthermore, transplanted DCs showed increased proliferation along with reduction in apoptosis as compared to untreated control. In conclusion, DCs showed better survival and regeneration potential as compared with ADSCs in rat model of OA and thus may serve a better option for regeneration of osteoarthritic cartilage.